Nitrogen dynamics and nitrogen use efficiency of old and modern oats - Muurinen, Susanna; Peltonen-Sainio, Pirjo (MTT, 2004)
Nitrogen (N) is one of the most important nutrients in crop production. The loss of nitrogen causes environmental pollution as well as economic losses. Therefore, cereal cultivars with more efficient N use are of special interest also in Finland. Three years study with three Finnish oat cultivars under two nitrogen (0 N and 90 N) fertilizer rates were conducted at MTT Agrifood Research Finland in Jokioinen. One landrace and two modern Finnish oat lines were tested. The modern cultivars differed by the plant height and grain protein content. The study investigated N uptake, N utilization and N dynamics of the three oat cultivars with emphasis on N use efficiency. N use was analysed at different growing stages from plants separated to main stem and tillers and further leaves, straw and panicles. Approximately over 87% of the total aboveground N at maturity was uptaken prior to anthesis in all three years and in both N rates. However, despite the lower grain yields, Aslak (modern cultivar) had highest N use efficiency of 29.3 kg kgN-1. Based on the stepwise regression of different N parameters calculated from anthesis to maturity, high N use efficiency was associated with N uptake efficiency. Instead low N use efficiency was associated with high main shoot straw N concentration and high N gained per cent to vegetative mass during the grain filling. These two latter parameters were particularly high on landrace cultivar released in 1920 s.
Keywords: Ka; typen käyttö; kaura; jalostus; lajike; typpi; lannoitus; NUE; Avena sativa; breeding; cultivar; nitrogen uptake efficiency